Normalization based on dependency diagram - Czenky, Márta (Teaching Mathematics and Computer Science, 2010)
Normalization is an important database planning method, although the understanding and application of this method brings up the utmost problem during data modelling. That is why we were looking for alternative normalization methods, from which the normalization with dependency diagram proved to be the most efficient. This was also confirmed by the statistical estimation of the carried out survey.